Uncovering the Complexity of Supply Chain in MSMEs: A Systematic Review - Rahardjo, Budi; ., Suliyanto; ., Daryono (Journal of Ecohumanism, 2025)
Supply chain management (SCM) obstacles frequently impede operations optimization for micro, small, and medium enterprises (MSMEs). Supply Chain Management significantly enhances the competitiveness and operational efficiency of Micro, Small, and Medium Enterprises; nevertheless, its adoption is frequently hindered by resource, financial, and technological limitations. This dilemma must be addressed by MSMEs, which are vital to economic growth, innovation, and job creation globally. This study analyzes the intricacies of SCM implementation in MSMEs via a comprehensive review of the current literature. The PRISMA framework delineates the comprehensive procedures for selecting and accepting pertinent articles. This review utilized a sample of 20 publications in the Scopus database, published between 2014 and 2023. An exhaustive examination of the literature on SCM identifies the most cited papers, journals, and authors. The author’s concluding point in this paper posits that, despite considerable research in SCM, it is imperative to modify conditions that can facilitate SMEs, particularly in developing nations.